FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA. - Gogor Mustawa Zais (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
The objective of this study was to find out and analyze the impact of stocks value, capital structure, profitability and liquidity on dividend policy in consumer goods industry companies in Indonesia Stock Exchange for a period of 2010 to 2014. The data were analyzed by using multiple regression. There were five variables in this research. A dependent variable was cash dividend policy is proxied by Dividend Payout Ratio (DPR) and independent variables were stocks value, capital stucture, profitability, and liquidity. The results showed that the stocks value and profitability variable have positive and significant impact on the dividend policy. This means that the higher the stocks value and the profitability, the company increased the dividend payments are also higher. Capital structure and liquidity variables of the company does not have a significant effect on the company's dividend policy in the consumer goods industry in Indonesia Stock Exchange for a period of 2010 to 2014.Keywords : Stocks Value, Capital Structure, Profitability, Liquidity, Dividend Policy